Exporting 'active citizenship': foreign support for citizenship education in the Arab world. Issue 5 (4th July 2019) - Geha, Carmen; Horst, Cindy
ABSTRACT: What explains the rise in support for active citizenship programs in the Arab region? How has active citizenship been envisioned and taught with support by foreign states? How do participants understand the usefulness and impact of such programs? In this paper, we examine the contexts in which citizenship programs that embody the political aspirations of foreign states, are implemented. Embedded in local political realities, participants in these programs routinely question the efﬁcacy and applicability of training modules focused on active citizenship and civic engagement. We argue that the proliferation of active citizenship programs for civil society organizations in practice serves to both bolster state legitimacy and discourage community leaders and activists from expressing political dissent. By submerging conﬂicting values, practices, and perspectives while encouraging civic participation based on conformity rather than dissent, active citizenship programs risk fostering a depoliticized civil society that is detached from the local political context.